Identifying the Big Questions in paleontology: a community-driven project - Smith, Jansen; Dowding, Elizabeth; Abdelhady, Ahmed A.; Abondio, Paolo; Araújo, Ricardo; Aze, Tracy; Balisi, Mairin A.; Buatois, Luis A.; Carvajal-Chitty, Humberto; Chattopadhyay, Devapriya; Coiro, Mario; Dietl, Gregory P.; et al. (Paleobiology, 2025)
Paleontology provides insights into the history of the planet, from the origins of life billions of years ago to the biotic changes of the Recent. The scope of paleontological research is as vast as it is varied, and the field is constantly evolving. In an effort to identify "Big Questions"in paleontology, experts from around the world came together to build a list of priority questions the field can address in the years ahead. The 89 questions presented herein (grouped within 11 themes) represent contributions from nearly 200 international scientists. These questions touch on common themes including biodiversity drivers and patterns, integrating data types across spatiotemporal scales, applying paleontological data to contemporary biodiversity and climate issues, and effectively utilizing innovative methods and technology for new paleontological insights. In addition to these theoretical questions, discussions touch upon structural concerns within the field, advocating for an increased valuation of specimen-based research, protection of natural heritage sites, and the importance of collections infrastructure, along with a stronger emphasis on human diversity, equity, and inclusion. These questions offer a starting point - an initial nucleus of consensus that paleontologists can expand on - for engaging in discussions, securing funding, advocating for museums, and fostering continued growth in shared research directions.
CRIS-Team Scopus Importer:2025-10-16